OP0098 Remission and maintenance of efficacy in a phase 2b study of vobarilizumab, an anti-interleukin 6 receptor nanobody, in patients with moderate-to-severe rheumatoid arthritis despite treatment with methotrexate. (15th June 2017) - Dörner, T; Weinblatt, M; Durez, P; Alten, R; Beneden, K Van; Dombrecht, EJ; Beuf, K De; Schoen, P; Zeldin, RK
Abstract : Background: Vobarilizumab is a Nanobody® consisting of an anti-IL-6R domain and an anti-human serum albumin domain in development for treatment of RA. The efficacy and safety were assessed in a 24-week double-blind global phase 2b study in patients with active RA on a stable background of MTX. Main efficacy and safety results were previously reported [1]. Objectives: To report the impact of treatment with vobarilizumab on secondary efficacy endpoints including SDAI and CDAI remission and the sustained response at 4 consecutive visits based on ACR50, ACR70 and DAS28CRP . Methods: Patients were randomized to receive subcutaneously administered placebo or 1 of 4 dose regimens of vobarilizumab in addition to MTX. SDAI and CDAI remission at Week 24 was evaluated, as was maintenance of efficacy as defined by sustained DAS28CRP <2.6 responses at 4 consecutive visits (i.e., at Weeks 12, 16, 20 and 24). In addition, a post-hoc analysis was performed on sustained ACR50 and ACR70 responses from Week 12 through Week 24. Proportions of patients achieving response for these endpoints were summarized by treatment group. Subjects with missing values were analyzed as non-responders. Results: A total of 345 patients were randomized. Demographics and baseline characteristics were similar across groups with mean baseline DAS28CRP between 5.8 and 6.2. At Week 24, up to 19% and 20% in the vobarilizumab groups reached CDAI and SDAI remission, respectively vs. 10% and 9% who received placebo (Table 1 ). At Week 24, up to 61% and 45% of the patients in the vobarilizumab groups achieved an ACR50 or ACR70 response, respectively (39% and 17% on placebo). Approximately one third of the randomized patients in the 3 highest treatment groups had a sustained ACR50 response from Week 12 through Week 24 (Table 2). Sustained remission defined by DAS28CRP <2.6 at 4 consecutive visits, i.e. at weeks 12, 16, 20 and 24, was observed in 20% to 25% of the patients in the 3 highest dosing arms compared with 3% of those receiving placebo. Conclusions: In patients with active RA, treatment with vobarilizumab at the 3 highest dose regimens in addition to MTX had a positive and sustained impact on disease activity through Week 24 as defined by clinically relevant efficacy endpoints. References: Weinblatt et al. (Annual Scientific Meeting, Canadian Rheumatology Association, 2017). Disclosure of Interest: T. Dörner Consultant for: Ablynx, M. Weinblatt Consultant for: Ablynx, P. Durez Consultant for: Ablynx, R. Alten Consultant for: Ablynx, K. Van Beneden Employee of: Ablynx, E. Dombrecht Employee of: Ablynx, K. De Beuf Employee of: Ablynx, P. Schoen Employee of: Ablynx, R. Zeldin Employee of: Ablynx